The Manso Glacier drainage system in the northern Patagonian Andes: an overview of its main hydrological characteristics - Pasquini, Andrea Ines (2012)
The Manso Glacier (~41°S, 72°W), in the northern Patagonian Andes of Argentina, is a regenerated glacier that, like many other glaciers in the region and elsewhere, has been showing a significant retreat. Glacial melt water feeds the Manso Superior River, which, before crossing the Andes to reach a Pacific outfall, flows through the Mascardi (a deep, oligotrophic and monomictic lake) and significantly smaller Hess and Steffen lakes. Harmonic analysis of Mascardi's lake level series suggests that the El Niño-Southern Oscillation signal has been strong during the 1985–1995 decade but has grown weaker during the initial decade of the 21st century. Hydrological trend analyses applied in data recorded in the uppermost reaches show a monthly and annual decreasing trend in the Manso Superior River discharge series and Mascardi's lake level, which are connected with both, decreasing melt water discharge and (austral) wintertime atmospheric precipitation. Downstream, the decreasing signal initially looses statistical significance and then, when flowing through Steffen Lake, reverses the lake level trend that becomes significantly positive. This suggests that, on its way to the Pacific Ocean, the Manso River receives abundant Andean snow melt water and atmospheric precipitation, which are sufficient to obliterate the negative trend recorded in the uppermost reaches. The reason for this local phenomenon is that the Manso is an antecedent river (aka superposed stream), and hence, the valley crossing the Andes allows the incursion of Pacific humidity that modifies the hydrological regime several hundred kilometres inland.